Talking smack : Honest Conversations About Drugs. - McMillen, Andrew ([West End, Qld.] : Andrew McMillen, 2014)
"Talking Smack features intimate interviews with some of Australia's best musicians, who share their thoughts on - and experiences with - illicit, prescription and legal drugs. By having conversations about a subject that's rarely discussed in public, and much less often dealt with honestly, the book explores the truths of a contentious topic that isn't going away ..."--About the book
Title from title screen (viewed on 3 June 2015)
Mode of access: Available online. Address as at 28/8/15
Selected for archiving
Keywords: Drugs and mass media -- Australia; Drugs and popular music -- Australia; Music trade -- Australia; Musicians -- Drug use -- Australia; Australian